Impact of specificity on cost-effectiveness of screening women at high risk of breast cancer with magnetic resonance imaging, mammography and ultrasound - Kaiser, Clemens G.; Dietzel, Matthias; Vag, Tibor; Rübenthaler, Johannes; Froelich, Matthias F.; Tollens, Fabian (European Journal of Radiology, 2021)
Purpose: Aim of this study was to analyze the comparative cost-effectiveness of MR-mammography vs conventional imaging in a screening setting for women with high risk of breast cancer, with particular focus on the impact of specificity of MRM. Method: Decision analytic modelling and Markov Modelling were applied to evaluate cumulative costs of each screening modality and their subsequent treatments as well as cumulative outcomes in quality adjusted life years (QALYs). For the selected time horizon of 30 years, false positive and false negative results were included. Model input parameters for women with high risk of breast cancer were estimated based on published data from a US healthcare system perspective. Major influence factors were identified and evaluated in a deterministic sensitivity analysis. Based on current recommendations for economic evaluations, a probabilistic sensitivity analysis was conducted to test the model stability. Results: In a base-case analysis, screening with XM vs. MRM and treatment resulted in overall costs of 36,201.57 vs. 39,050.97 and a cumulative effectiveness of 19.53 QALYs vs. 19.59 QALYs. This led to an incremental cost-effectiveness ratio (ICER) of 45,373.94 per QALY for MRM. US and XM + US resulted in ICER values higher than the willingness to pay (WTP). In the sensitivity analyses, MRM remained a cost-effective strategy for screening high-risk patients as long as the specificity of MRM did not drop below 86.7 %. Conclusion: In high-risk breast cancer patients, MRM can be regarded as a cost-effective alternative to XM in a yearly screening setting. Specificity may be an important cost driver in settings with yearly screening intervals.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Breast cancer; Clinical breast examination; High-Risk screening; Mammography; MR-Mammography; Ultrasound